Pertimbangan Hukum Hakim Dalam Menetapkan Suatu Putusan di Persidangan Perkara Pidana - Lubis, Andi Hakim; Hasbi, Mhd. (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One of the important aspects of a judge's decision in judicial power is the judge's consideration in giving the severity of a criminal sentence. The judge's consideration can be interpreted as an opinion about the good or bad of a matter in order to provide a decision or decision that is sentenced by a judge at the supreme court and judges at the lower judicial bodies as outlined by the judge in his decision. The judge's considerations are the thoughts or opinions of the judge in making a decision by looking at things that can lighten or burden the offender. Every judge is obliged to submit written considerations or opinions on the case being examined and becomes an integral part of the decision. The type of research used in this dissertation is normative research. The essence of the judge's own decision is the crown, and the peak of the criminal case so that the judge in giving a criminal decision must pay attention to all aspects. In the judge's consideration, there are 3 (three) aspects that the judge considers, namely juridical, philosophical and sociological aspects.